Hubungan antara Motivasi Berwirausaha dengan Sikap Kewirausahaan bagi Mahasiswa Jurusan Teknik Otomotif Fakultas Teknik Universitas Negeri Padang - Nuzul Hidayat; Ganefri Ganefri; Asmar Yulastri; Muslim Muslim; Muhammad Yasep Setiawan (Universitas Negeri Padang, 2022)
The purposes of this study are to (1) describe the entrepreneurial spirit of automotive engineering students, (2) describe the motivation of the entrepreneurial spirit of automotive engineering students, and (3) see whether entrepreneurship and motivation have a relationship between For automotive engineering students This research is a descriptive analysis research. , regression and correlation, data collection was carried out using questionnaires and literature studies as additional data. In this study, the sample was 8th semester students as many as 35 students. Survey Results (1) The level of student entrepreneurship attitude for entrepreneurship is 71.36% in the